2020
DOI: 10.3390/microorganisms8091345
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relatedness and Diversity of Staphylococcus aureus from Different Reservoirs: Humans and Animals of Livestock, Poultry, Zoo, and Aquaculture

Abstract: The main aim of this study was the characterization of antibiotic resistance mechanisms in 82 Staphylococcus aureus strains isolated from humans and animals. Antibiotic susceptibility testing was performed on all S. aureus isolates accordingly, and antibiotic-resistant genes were investigated by genotypic methods. The genetic diversity of S. aureus was studied through spa, multilocus sequence typing (MLST), and agr typing methods. The majority of S. aureus from human sources were resistant to cefoxitin (and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 75 publications
4
13
1
Order By: Relevance
“…The twenty spa types observed among the human in our study agrees with other reports elsewhere showing presence of multiple spa types among the MRSA isolates [25], [27]. However, differences has been observed in the spa types where we observed presence of; t1081, t701, t034, t041, t044, t037, t4677, t127, t1451, t9377, t032, t121, t922, t019, t108, t002, t030, t018, t040 and t012 in our region, while Vanessa et al reported t008, t020, t022, t104, t179, t718, t747, t910, t932, t1094, t2357, t5624, t10683 and t14933 in Portugal [24].This suggests diverse genetic backgrounds and multiple routes of their acquisition and spread. In addition, this is inconsistent with a systematic review of the global distribution of spa types which revealed that t064 and t037 were the most prevalent spa types in Africa [28], yet t064 was not observed and t037 was not signi cantly high.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…The twenty spa types observed among the human in our study agrees with other reports elsewhere showing presence of multiple spa types among the MRSA isolates [25], [27]. However, differences has been observed in the spa types where we observed presence of; t1081, t701, t034, t041, t044, t037, t4677, t127, t1451, t9377, t032, t121, t922, t019, t108, t002, t030, t018, t040 and t012 in our region, while Vanessa et al reported t008, t020, t022, t104, t179, t718, t747, t910, t932, t1094, t2357, t5624, t10683 and t14933 in Portugal [24].This suggests diverse genetic backgrounds and multiple routes of their acquisition and spread. In addition, this is inconsistent with a systematic review of the global distribution of spa types which revealed that t064 and t037 were the most prevalent spa types in Africa [28], yet t064 was not observed and t037 was not signi cantly high.…”
Section: Discussioncontrasting
confidence: 47%
“…However, emphasis should be put on to cattle and swine hygiene through constant kraal or pen cleaning, proper sanitation and disinfecting to reduce MRSA colonization. MRSA among livestock has been reported before [23] and its signi cance in zoonotic transmissions should not be disregarded [22].The diversity of MRSA is expanding, and detecting lineages of human origin in animals and vice-versa becoming more common [24] and in our current study, we identi ed 20 spa types from both humans and Livestock. A similar partner of diversity has been reported in Serbia among community and livestock according to Cirkovic et al [25].…”
Section: Discussionmentioning
confidence: 65%
“…In this review, it appears that storks and rodents could be the major wild animal reservoirs of this MSSA genetic lineage (mainly with the spa type t571) [ 17 , 37 ]. It is worthy to remark that MSSA-CC398 isolates have been recovered from other animals, such as the aquatic ones [ 63 , 66 ]. From the phylogenetic and evolutionary point of view, the CC398 lineage of S. aureus was postulated to have two separate host sub-clades: (a) a livestock associated-clade in which S. aureus -CC398 carries the mecA and tetM genes and lacks the scn gene (associated to phage φ3-Sa) and (b) a human associated-clade (MSSA) carrying scn (human adaptation gene) but no tetM [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al (2020) mentioned that adaptation of different phylogenetic lineages of S. aureus in wild animals is probably associated with genetic diversification of the circulating strains that could add a risk of dissemination of the emerging livestockassociated-MRSA lineages. A wide variety of animals besides humans have the potential to harbour novel strains of S. aureus, which could enter the human population, or conversely, humans may pass S. aureus strains to animal species, which can then acquire additional resistance patterns (Salgueiro et al, 2020). In this study, all the examined isolates of S. aureus were completely resistant to amoxicillin, oxacillin and ampicillin (MRSA), and 31 (93.94%) of isolates were resistant to cefoxitin which is considered the best marker for mecA-mediated methicillin resistance.…”
Section: Discussionmentioning
confidence: 99%